Studies in natural products chemistry. - Rahman, Atta-ur-, 1942- (Studies in natural products chemistry, 2021)
Studies in Natural Products Chemistry, Volume 69 covers the synthesis, testing and recording of the medicinal properties of natural products, providing cutting-edge accounts of fascinating developments in the isolation, structure elucidation, synthesis, biosynthesis and pharmacology of a diverse array of bioactive natural products. Natural products in the plant and animal kingdom offer a huge diversity of chemical structures that are the result of biosynthetic processes. With rapid developments in spectroscopic techniques and accompanying advances in high-throughput screening techniques, it has become possible to rapidly isolate and determine the structures and biological activity of natural products, thus opening up opportunities in drug development.